ADSORPTION CAPACITY OF RICE HUSK FOR SILVER IONS BY LANGMUIR ISOTHERM METHOD - Zafar, S.; Mirza, M. L.; Khalid, N. (The Nucleus, 2011)
The adsorption of silver ions on rice husk has been studied in nitric acid medium at ambient temperature using batch method. Atomic absorption spectrometry was employed for the quantification of silver ions. Maximum adsorption was observed at nitric acid concentration of 0.001mol L−1 using 0.5 g of rice husk and shaking time of 15 minutes. The adsorption of silver ions obeyed the Langmuir isotherm model in the concentration range of 1.854 × 10−4 to 1.159 × 10−3 mol L−1 . A comparison of four linear equations of the Langmuir isotherm (Type 1, 2, 3 and 4) were examined for silver ion sorption onto rice husk. Isotherm parameters obtained from the four linear equations are reported and discussed. Though Langmuir type 1 is the most popular form, but the type 2 had the highest correlation coefficient of R2 = 0.9967, compared with the other Langmuir linear equations with R2 values ranged from 0.9688 to 0.9937. The observed adsorption capacities (Qm) of the silver ions on rice husk were in the range of 1.08 to 1.62 mg g−1 . The determined adsorption capacity of silver on rice husk was also compared with the reported values for other adsorbents.